Sistem Pendukung Keputusan Calon Penerima Bantuan Program Keluarga Harapan (PKH) Desa Karangsari Menggunakan Metode Analytical Hierarchy Process (AHP) - Rio Wahyudin; Otong Saiful Bahri; Nur Ariesanto Ramdhan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This research focuses on developing a decision support system to determine recipients of the Family Hope Program (PKH) more objectively and systematically. The main problem faced by the aid program is the manual recipient selection process, which has the potential to lead to inaccurate targeting. The method used in this research is the Analytical Hierarchy Process (AHP), which is able to process various criteria through a weighting process and pairwise comparisons. The data used in this study amounted to 273 prospective aid recipients, analyzed based on nine criteria. The results show that the developed system is able to generate an automatic ranking of prospective aid recipients based on preference values. Thus, this system can help improve accuracy, transparency, and efficiency in the decision-making process.